The role of metacognitive skills in solving object-oriented programming problems: a case study - Havenga, Marietjie (Journal for Transdisciplinary Research in Southern Africa, 2015)
This article reports on the role of metacognitive skills when solving object-oriented programming problems as part of a case study. The research was constructivist-based within an interpretivist approach to explore how four students constructed their own thinking when solving programming problems. A qualitative methodology was employed. Both concept-driven coding and data-driven coding were applied. Two main issues emerged from the findings. Participating students had fragmented knowledge of the object-oriented approach and shortcomings regarding the implementation thereof, and they experienced problems with metacognitive control during all the steps of program development. Based on the findings the use of metacognitive critical control points (MCCPs) is proposed to be used as a mechanism to facilitate students in their programming efforts and to prevent loss of control during program development.